Differential gene expression and identification of growth-related genes in the pituitary gland of South African goats - Ncube, Keabetswe T.; Dzomba, Edgar F.; Rosen, Ben D.; Schroeder, Stephen G.; Van Tassell, Curt P.; Muchadeyi, Farai. C. (Frontiers in Genetics, 2022)
Growth and carcass quality are economically important traits in goat production. This study investigated differentially expressed genes from the caprine pituitary gland transcriptome of South African indigenous goat breeds of varying growth performances and carcass quality parameters. Tissues were harvested from the pituitary gland of three South African Boer goats and three village ecotype goats all raised under similar conditions simulating intensive commercial production systems. Three additional tissues were harvested from village ecotype goats that were raised extensively on village farms. Between breed differences were investigated by comparing differential gene expression among three South African Boer and three village goats that were both raised under intensive commercial production system at a research farm. Within-breed differences were investigated by comparing differential gene expression among three village goats raised under extensive conditions (on-farm in Pella, S.A. village farming community) and three village goats raised under intensive commercial production system (at ARC research farm in Pretoria, South Africa. Total RNA was isolated from the pituitary gland of 36-week-old animals (n=9) and sequenced individually in triplicates. An average of 28,298,512 trimmed, and quality-controlled reads/animal were mapped to the goat genome (Capra_hircus.ARS1.94) using HiSat2 software. Transcript assembly and quantification yielded 104 differentially expressed genes for village goats raised under extensive system and 62 for village goats raised under the intensive production system at the false discovery rate (FRD) of 0.05 and a fold change of 2. Growth-related genes such as POU3F4 and TSHZ1 were highly expressed within breeds raised under both production systems. Conversely, growth-related genes such as FGFR2 and SMPX genes were highly expressed between breeds raised under similar production systems. Ballgown analysis revealed a high expression of GH1 and IGF1 in the intensively raised compared to extensively raised goats. Both genes were also highly expressed in the village goats when compared to the Boer. The differential gene expression data provided insights into genes and molecular mechanisms associated with growth and growth development in goats.